2023
DOI: 10.1037/drm0000234
|View full text |Cite
|
Sign up to set email alerts
|

Predicting impactful dreams: The contributions of absence-related melancholy and absence-related depression.

Abstract: Distressing life events precipitate disturbing dreams in several forms (e.g., nightmares, sleep terrors). Although research has focused on nightmares, some studies have differentiated three types of impactful dreams: nightmares, existential dreams, and transcendent dreams (Kuiken et al., 2006; Lee & Kuiken, 2015). In two studies, we examined whether contrasting forms of response to distressing life events (absence-related depression and absence-related melancholy) differentially predict these dream types. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Kuiken and colleagues [17] articulated such a dual process model, although empirical support remains limited to studies that rely on self-report rather than neurophysiological evidence of ANSmodulated attentional adjustments. First, the balance of sympathetic and parasympathetic ANS activation plausibly influences the sensory modalities that predominate in the transformations within each dream type.…”
Section: Impactful Dream Types: Manifest Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuiken and colleagues [17] articulated such a dual process model, although empirical support remains limited to studies that rely on self-report rather than neurophysiological evidence of ANSmodulated attentional adjustments. First, the balance of sympathetic and parasympathetic ANS activation plausibly influences the sensory modalities that predominate in the transformations within each dream type.…”
Section: Impactful Dream Types: Manifest Contentmentioning
confidence: 99%
“…A distinctive form of metacognition may give the spontaneous transformations of existential and transcendent dreams their epistemic import. There is replicable evidence [14,15,17,18] that existential dreams and transcendent dreams involve a form of reflective awareness in which dreamers sense themselves from two points of view (e.g., "I became split into two parts; I was able to experience the dream world from either perspective"). Such dual attunement not only departs from the singlemindedness of typical dreams [33] but also from the concurrent awareness of dreaming that is the allure of lucid dreaming [34].…”
Section: Dual Perspectivesmentioning
confidence: 99%
“… * Table entries capture the gist of (a) two phenomenological studies involving a combination of first-person rating scales and open-ended dream description [ 14 , 15 ] and (b) three studies involving rating scales for the features identified in the original phenomenological studies [ 16 , 17 , 18 ]. …”
Section: Tablementioning
confidence: 99%
“…A distinctive form of metacognition may give the spontaneous transformations of existential and transcendent dreams their epistemic import. There is replicable evidence [14,15,17,18] that existential dreams and transcendent dreams involve a form of reflective awareness in which dreamers sense themselves from two points of view (e.g., "I became split into two parts; I was able to experience the dream world from either perspective"). Such dual attunement not only departs from the single-mindedness of typical dreams [33] but also from the concurrent awareness of dreaming that is the allure of lucid dreaming [34].…”
Section: Dual Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation